Internet of Things untuk Sistem Pemantauan Kualitas Air pada Kolam Ikan Lele pada Pembudidaya TDR Sultan Adam Banjarmasin - Yuslena Sari; Eka Setya Wijaya; Andreyan Rizky Baskara; Muhammad Syauqi Al Fath; Muhammad Andri Firdaus (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2023)
TDR Catfish Farmer Sultan Adam Banjarmasin is a home industry (IRT) engaged in the business of catfish farming located on Jl. Sultan Adam No.17 RT.22, Surgi Mufti, North Banjarmasin. In the management of catfish farming, water quality is an important factor in the success of cultivation where poor water quality can cause fish to be more susceptible to disease. Apart from these needs, the TDR of Sultan Adam Catfish Farmers actually has problems in the process of monitoring pond water quality conditions which are currently carried out manually and periodically by breeders. This process is considered ineffective because it is difficult to determine water quality from the physical condition of the water which changes rapidly due to weather or fish feed residue. The solution offered to solve this problem is to develop a tool that can monitor temperature conditions and the acidity of catfish pond water automatically and in real time. This innovation was developed by utilizing the Internet of Things (IoT) through the use of the DS18B20 temperature sensor and SS15 pH sensor on the ESP32 WROOM-32D microcontroller. The results of system testing from fuzzy logic calculations at the output of the microcontroller and Matlab and the suitability of expert information in determining pool water quality obtained an average error value of 0.46%. Based on these results, it can be concluded that the IoT-based water quality monitoring system in determining water quality is suitable for direct use.